Development and techno-economic assessment of a new biomass-assisted integrated plant for multigeneration. (15th December 2019) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Highlights: A new renewable energy assisted multigeneration plant is introduced for useful commodities. A biomass assisted combined plant is analyzed in terms of thermodynamic and economic viewpoints. The whole energetic and exergetic performances of examined plant are 63.84% and 59.26%, respectively. The overall purchase cost rate of suggested cycle is about 2000 /s. Abstract: In this paper, a novel renewable power-assisted multigeneration system is introduced for useful commodities such as cooling, hydrogen, heating, drying, hot water, and power generations. The biomass energy is preferred as a renewable power source. The proposed plant is including the biomass gasifier unit, gas turbine cycle, Kalina cycle, reverse osmosis unit, proton exchange membrane electrolyzer, absorption cooling cycle, dryer and heat pump subsystem. The primary purpose of this paper is to analyze a biomass assisted combined plant in terms of thermodynamic and economic viewpoints. In this regard, the thermodynamic performance, exergy destruction rate and economic examination are performed according to the various parameters. Results demonstrated that the whole energy and exergy efficiencies of the examined plant are 63.84% and 59.26%, respectively. Furthermore, the total irreversibility and hydrogen production rates are found as 53, 406 kW and 0.072 kg/s. The overall purchase cost rate of the suggested cycle is about 2000 /s.